Crisis, imbalances, and India - Rajiv Kumar; Pankaj Vashisht (Asian Development Bank Institute (ADBI), 2011)
With the revival of global economy, the issues of exit policies and rebalancing global growth have taken center stage in policy discussions. Since many emerging Asian economies presently have large current account surpluses, the issue of rebalancing has special significance for Asia. While India, like other Asian economies, suffered only an indirect impact from the financial crisis, its current policy challenges appear to be different from those facing the People's Republic of China (PRC) and other East Asian economies, which have relied heavily on external demand and access to the US market for their growth momentum. With a negative contribution of net exports to gross domestic product growth along with foreign exchange reserves, which amount to a mere one-ninth of the PRC's, the issue of Trans-Pacific rebalancing of economic growth does not have the same connotations for India as it does for other East Asian economies. However, this paper argues that, given its large domestic market, India could help other East Asian economies in their efforts to achieve greater export diversification and rebalancing of growth.
Keywords: G01; E66; F15; 330; Finanzmarktkrise; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Außenhandelsliberalisierung; Wirtschaftspolitik; Wirtschaftswachstum; Indien; Vergleich; Asien